2022
DOI: 10.1039/d2nj02336a
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole and a polypyrrole/nickel oxide composite – single-walled carbon nanotube enhanced photocatalytic activity under visible light

Abstract: A novel NiO/PPy/SWCNT composite for removal of organic dyes with an emphasis on the effect of photocatalytic charge carrier transport and photoluminescence properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 95 publications
2
32
0
Order By: Relevance
“…The h + plays a crucial role in decomposing CR into simpler ones. Electrons move from the VB of CP to the conduction band (CB), with the CB potential relative to NHE approximately at −0.54 V and −0.63 V. The electrons in the CB of CPs react with O 2 molecules dissolved in the dye solution, forming superoxide radical anions (˙O 2 − ), since the reduction potential of O 2 to ˙O 2 − is −0.18 V vs. NHE, 47 which is lower than the CB of CPs. These superoxide radicals react with H 2 O and transform into H 2 O 2 (˙O 2 − /H 2 O 2 , +0.91 V vs. NHE).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The h + plays a crucial role in decomposing CR into simpler ones. Electrons move from the VB of CP to the conduction band (CB), with the CB potential relative to NHE approximately at −0.54 V and −0.63 V. The electrons in the CB of CPs react with O 2 molecules dissolved in the dye solution, forming superoxide radical anions (˙O 2 − ), since the reduction potential of O 2 to ˙O 2 − is −0.18 V vs. NHE, 47 which is lower than the CB of CPs. These superoxide radicals react with H 2 O and transform into H 2 O 2 (˙O 2 − /H 2 O 2 , +0.91 V vs. NHE).…”
Section: Resultsmentioning
confidence: 99%
“…The possible mechanisms of interaction between CP 1 and solvent-free CP 2 with dyes are as follows: 47,48 hν + CPs → (h VB + + e CB − ) CPsh VB + + H 2 O → ˙OH + H + h VB + + Dye CR → colorless degraded productsO 2 + e − → ˙O 2 − (O 2 /˙O 2 − = −0.18 V vs. NHE)˙O 2 − + H 2 O → HOO˙ + OH − H 2 O + HOO˙ → H 2 O 2 + ˙OH (˙O 2 − /H 2 O 2 = +0.91 V vs. NHE)H 2 O 2 + e − → ˙OH + OH − (H 2 O 2 /˙OH = +0.39 V vs. NHE)H 2 O 2 + h + → HOO˙ + H + HOO˙ + H 2 O 2 → H 2 O + O 2 + ˙OHDye + hν → Dye*(e LUMO − + h HOMO + )Dye*(e LUMO − + h HOMO + ) + (h VB + ) CP → CP + Dye + Dye + (h HOMO + ) + ˙OH/˙O 2 − → colorless degraded products…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 In our previous work, it has been reported that conducting polymer PPy as a cocatalyst imparts substantial enhancement in the visible light-assisted photocatalytic activity by loading NiO nanoparticles with single-walled carbon nanotubes (SWCNTs) toward organic pollutant degradation. 23 The importance of PPy in photocatalysis for its good electrical conductivity and excellent charge transport properties is due to its delocalized π conjugated electrons. 24,25 Additionally, PPy is highly stable under an ambient environment, has a comparatively low bandgap (E g ∼ 2.4 eV) for working in solar optical energy windows, and has an appropriate band edge potential level for proton reduction.…”
Section: ■ Introductionmentioning
confidence: 99%